Highly stable vortex state in sub-100 nm nanomagnets - Wang, Xinghua (2013)
We report on the magnetization reversal process in sub-100 nm Ni80Fe20 asymmetric ring. The switching mechanism involves a stable vortex state due to the strong anisotropy imposed on the narrow arm of the ring. Experimental demonstration shows that such vortex configuration does not annihilate until a large reversal field of 1200 Oe. The asymmetry of the structure promotes a unique reversal process, which gives us control over the chirality of the vortex configuration. Micromagnetic simulations reveal that the highly stable vortex configuration is sustainable in the asymmetric ring structures with a diameter as small as 30 nm.